PERBEDAAN DURASI MENGEMUDI, POSTUR TUBUH DAN KEBIASAAN MEROKOK DENGAN KELUHAN LOW BACK PAIN (LBP) PADA PENGEMUDI BUS - Nadia Rahmani; Sri Kubillawati (JURNAL KESEHATAN DAN KEBIDANAN, 2022)
Low Back Pain (LBP) is pain felt in the lower back whose source is the spinal column (lower back), muscles, nerves, tendons, joints, or cartilage. LBP complaints to drivers are caused by several stressors such as demographic factors, vehicle physical design factors, work factors and environmental factors. This research is an analytical study with a quantitative approach using a cross sectional design. The population of all bus drivers at Cileungsi Bus Terminal is 32 people, the sample used is total sampling. Analysis using chi-square test. The results of the study stated that there was a significant relationship between driving duration, posture and smoking habits with complaints of LBP. Driving duration is the most dominant variable affecting LBP complaints. To reduce the complaints of LBP pain, it is hoped that it can improve a healthy life. To improve health, it is necessary to pay attention to the duration of work, posture when driving and reduce smoking habits. Conduct health promotions on occupational health and safety, especially regarding correct driving attitudes and the dangers of low back pain to bus drivers.